Paintings in Proust - Karpeles, Eric (Thames & Hudson, 2008)
Paintings in Proust is a companion guide to a monumental twentieth century work of art. Marcel Proust's In Search of Lost Time, one of the most expansive literary creations ever composed, is a vast novel teeming with visual references. Author Eric Karpeles has combined his experiences as painter and writer to create a lavishly illustrated book that illuminates the winding corridors of Proust's singular, labyrinthine masterpiece. For newcomers to Proust's work, Paintings in Proust functions as a complementary guidebook, providing a firmer ground from which to undertake the task of plunging into a novel famously known for its complexity and its length. At the same time, Paintings in Proust offers further nourishment to the seasoned Proustian reader, whose plate is already extravagantly full. Paintings in Proust animates the experience of reading by revealing and clarifying much that might otherwise remain obscure. Illustrating a treasure trove of visual references, Paintings in Proust provides access and insight in its presentation of paired groupings of texts and pictures, arranged sequentially, as they appear in volume after volume of In Search of Lost Time.
Includes bibliographical references (p. 329-344) and index
Keywords: Proust; Marcel / 1871-1922 / À la recherche du temps perdu; Proust; Marcel / 1871-1922 / Criticism and interpretation; Proust; Marcel <1871-1922>; Proust; Marcel; À la recherche du temps perdu; Painting in literature; Painting; Schilderijen; À la recherche du temps perdu (Proust); Malerei; Ikonographie; Ekphrasis